Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.2478/v10181-011-0013-z
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory diagnosis of mycoplasma infection in young cattle

Abstract: The aim of this study was to detect Mycoplasma species in the respiratory tract of 110, 310 and 510 day-old groups of cattle by serological, bacteriological and histopathological investigations. Antibodies against M. bovis were found in 75% of the 110 day-old, in 50% -of the 310 day-old and in 55% -of the 510 day-old groups of cattle.Bacteriological examination of the samples from nasal cavities revealed that Mycoplasma carriers were found in 60% of the 110 day-old group of cattle, 40% of the 310 day-old and 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 20 publications
(25 reference statements)
0
11
1
Order By: Relevance
“…DNA from isolated microorganisms was extracted with a 5% Chelex solution (Sigma, USA). Isolated microorganisms were analyzed by PCR using the forward primer, MW28 (5'-CCAGACTCCTACGGGAGGCA-3') and reverse oligonucleotide primer MW29 (5'-T GCGAGCATACTACTCAGGC-3') (Grida Lab, Lithuania) that are specific for the Mollicutes class (Bashiruddin et al 2005;Gabinaitiene et al 2011). This primer pair generates a 560 bp product.…”
Section: Mycoplasma Bovis Isolationmentioning
confidence: 99%
See 1 more Smart Citation
“…DNA from isolated microorganisms was extracted with a 5% Chelex solution (Sigma, USA). Isolated microorganisms were analyzed by PCR using the forward primer, MW28 (5'-CCAGACTCCTACGGGAGGCA-3') and reverse oligonucleotide primer MW29 (5'-T GCGAGCATACTACTCAGGC-3') (Grida Lab, Lithuania) that are specific for the Mollicutes class (Bashiruddin et al 2005;Gabinaitiene et al 2011). This primer pair generates a 560 bp product.…”
Section: Mycoplasma Bovis Isolationmentioning
confidence: 99%
“…M. bovis is also present in the respiratory tract of healthy cattle where it causes a subclinical upper respiratory infection and may provoke mastitis and metritis in caws and arthritis or tenosinovitis in fattening cattle (Fox et al 2005;Gagea et al 2006). From 2007 through to 2009, studies in Lithuania revealed that M. bovis was present in the upper respiratory tract of 52.5 percent (%) of healthy cattle (Gabinaitiene et al 2011). …”
mentioning
confidence: 99%
“…12 After stressful situations, M. bovis becomes pathogenic and clinical signs of BRD are observed, especially in young calves. 13 M. dispar was first isolated from pneumonic lungs of cattle, 14 and it has been described as a potential pathogen associated with BRD. 15,16 Considering the importance of Mycoplasma spp.…”
mentioning
confidence: 99%
“…Unpublished manuscript: The University of Sydney, Sydney School of Veterinary Science, Faculty of Science; 2017). Lastly, in a study involving the examination of 3 age groups (110, 310, and 510 days old) of male cattle for M. bovis on a breeding station, a higher percentage of animals were identified as positive by ELISA in serum samples (75, 50, and 55%) than by culture from samples taken from the nasal cavity (52, 30, and 27%) . These studies demonstrate that while the number of animals exposed to M. bovis may be high, the proportion of animals that succumb to disease or are actively shedding the pathogen is frequently much lower.…”
Section: Serological Diagnosismentioning
confidence: 83%